2021
DOI: 10.3389/feart.2021.638594
|View full text |Cite
|
Sign up to set email alerts
|

Diagenesis of Magnetic Minerals in Active/Relict Methane Seep: Constraints From Rock Magnetism and Mineralogical Records From Bay of Bengal

Abstract: In this study, we conducted a comprehensive investigation of rock magnetic, mineralogical, and sedimentological records of sediment cores supplemented by a high resolution seismic data to elucidate the controls of structural and diagenetic (early vs. late) processes on the sediment magnetism in active and relict cold seep sites in the Bay of Bengal. Two distinct sediment magnetic zones (Z-I and Z-II) are defined based on the down-core variations in rock magnetic properties. The sediment magnetism is carried by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 154 publications
1
7
0
1
Order By: Relevance
“…Our IRM and thermal demagnetization results are consistent with the extensive work of Badesab et al (2017Badesab et al ( , 2019Badesab et al ( , 2020, Dewangan et al (2013), Gaikwad et al (2021), João et al (2021), and Usapkar et al (2014) who used IRM and additional rock magnetic parameters (e.g., anhysteric remanent magnetization (ARM), and S-ratio) coupled with XRD and SEM EDS to document a dominant presence of titanomagnetite and minor amounts of hematite and goethite in the magnetic assemblages of the Krishna-Godavari Basin, with distinct intervals bearing magnetic iron sulfides and pyrite as diagenetic overprints. These comprehensive rock magnetic studies include Site MD-161 (Dewangan et al, 2013) which is about 100 m from NGHP-01 Site 10, and NGHP-01 Site 07 (Badesab et al, 2019), which is 8 km to the south of NGHP-01 Site 16.…”
Section: Reconstructing Detrital Magnetic Susceptibilitysupporting
confidence: 89%
See 1 more Smart Citation
“…Our IRM and thermal demagnetization results are consistent with the extensive work of Badesab et al (2017Badesab et al ( , 2019Badesab et al ( , 2020, Dewangan et al (2013), Gaikwad et al (2021), João et al (2021), and Usapkar et al (2014) who used IRM and additional rock magnetic parameters (e.g., anhysteric remanent magnetization (ARM), and S-ratio) coupled with XRD and SEM EDS to document a dominant presence of titanomagnetite and minor amounts of hematite and goethite in the magnetic assemblages of the Krishna-Godavari Basin, with distinct intervals bearing magnetic iron sulfides and pyrite as diagenetic overprints. These comprehensive rock magnetic studies include Site MD-161 (Dewangan et al, 2013) which is about 100 m from NGHP-01 Site 10, and NGHP-01 Site 07 (Badesab et al, 2019), which is 8 km to the south of NGHP-01 Site 16.…”
Section: Reconstructing Detrital Magnetic Susceptibilitysupporting
confidence: 89%
“…These studies document losses in fine‐grained titanomagnetite, precipitation of pyrite and greigite/pyrrhotite, and relative increases in high‐coercivity minerals in zones affected by H 2 S‐related diagenesis. In addition, numerous gravity cores collected throughout the KG‐Basin show titanomagnetite with reduced magnetic susceptibility or greigite presence at seep sites (Gaikwad et al., 2021; Usapkar et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…This observation is in agreement with available thermodynamic models (Machel, 1995), that suggest the preservation and/or precipitation of iron-oxides in sediments that are located around hydrocarbon accumulations, and the instability of these minerals in the reservoir itself. Also, the requirements for greigite's preservation are high concentrations of reactive iron, "small" amounts of organic carbon present and low levels of sulphides relative to the amounts of reactive iron (Kao et al, 2004;Gaikwad et al, 2021) and these will more likely be met in the "proximal" shales. Lepidocrocite was found to co-exist with greigite (Figure 9E) reiterating what has been found in another study (Minyuk et al, 2013).…”
Section: Provenance Of the Magnetic Mineralsmentioning
confidence: 99%
“…Many studies have shown that hydrocarbon migration into sedimentary rocks results in magnetic mineral diagenesis (e.g., Elmore et al, 1987;Machel, 1995;Liu et al, 2006a;Badejo et al, 2021c;Gaikwad et al, 2021), however, the product of this process has revealed significant variability in minerology and susceptibility along this migration pathway. Enhancement and destruction of magnetic signature has been reported for different environments, e.g., the formation of magnetite resulting in over an order increase in magnetization in the hydrocarbon saturated sediments of the Ordovician Arbuckle Group in South Oklahoma (Elmore et al, 1987), the replacement of authigenic iron oxides by pyrite resulting in diminished magnetization in the Cenozoic sandstones of south west Texas (Reynolds et al, 1993), and the formation of hydrocarbon related authigenic maghemite in the Mawangmiao Oil Field, Jianghan Basin, China (Liu et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…As emanações de metano provocam a dissolução redutiva dos minerais magnéticos detríticos primários convertendo-os em sulfetos de ferro, e consequentemente causando uma diminuição no sinal magnético dos sedimentos (Canfield e Berner, 1987;Gaikwad et al, 2021).…”
Section: Introductionunclassified